Dynamic Analysis of Semi-submersible Under the Postulated Failure of Restraining System with Buoy - Chandrasekaran, S. (Korean Society of Steel Construction, 2021)
Coupled dynamic analyses of a deep-water Semi-submersible platform, in the South China Sea region, is carried out under postulated damage of the restraining system for both 10 and 100-years return period events. Under the combined action of wind, wave, and current loads, motion responses of Semi-submersible at 1500 and 2000Â m water depths are analyzed in time-domain. Dynamic tension variations in the mooring lines are investigated for a fatigue failure using the SâN curve approach. Inclusion of a submerged buoy in the mooring system resulted in a marginal increase of the response due to a reduction in the restoration force of the mooring lines; submerged buoy also resulted in additional damping. The results of numerical studies showed an increase in tension in the mooring lines, which are adjacent to the damaged ones, causing reduced fatigue life. With the inclusion of submerged buoy in the mooring system, there is a considerable decrease in tension variation in mooring lines, increasing fatigue life. Failure of a mooring line causes an increase in tension of the adjacent mooring line, but not valid under all circumstances. It is seen from the studies that despite the postulated failure induced in a mooring, the adjoining line remains unaffected due to a steady coupling motion of the platform. Â© 2020, Korean Society of Steel Construction.